Antecedents and outcomes of resources recombination in the context of higher education industry at United Arab Emirates - Bibi, Dilnaz (2019)
Given the paradigm shift in the United Arab Emirates’ (UAE) economy from a fuel-based model to a service-based model made it worthy to examine what was happening in the UAE higher education sector where the UAE currently devotes approximately 25 percent of the total of federal government spending tons on education and the overall literacy rate is 90%. (Wikipedia.org). Coupled with quest towards a knowledge-based economy, lack of clear RR measurement scale, and the increased need for competitiveness in the higher education sectors, has called for the need to study the resources reconfiguration in UAE higher education institution (HEI) competitiveness.